Case Report: DRESS Syndrome Induced by Two Antituberculosis Drugs in an 8-Year-Old Girl - Urbonas, Vaidotas; Varnas, Dominykas; Mociskiene, Kristina; Kvedariene, Violeta; Rudzeviciene, Odilija (Frontiers in Pediatrics, 2022)
DRESS syndrome is defined as drug-induced hypersensitivity syndrome with rash, eosinophilia, and systemic symptoms. This syndrome is mostly associated with anticonvulsants, antibacterial and anti-inflammatory drugs. DRESS syndrome is a rare disease and is more frequently seen in adults. We present the first case report of DRESS syndrome in an 8-year-old girl, after 3 months of treatment with isoniazid and rifampicin. After discontinuation of drugs and a short course of prednisolone the girl recovered. After 5 years of follow-up, she is healthy and has no complaints but patch tests with isoniazid and rifampicin remain positive. The reported case emphasizes the importance of thorough medical history and including drug reactions in differential diagnosis.